Color Choice Game Program in C ++ Builder - Khaydarov Sherali Islam oglu; Khushbokova Saodat Kuchkor qizi; Abdisalomova Shahriniso Abdisalomovna (Peerian Journals Publishing, 2022)
This article discusses the color selection game program in c ++ builder and its functions, Image - the ability to place a graphic image anywhere on the object form
Keywords: Canvas; Brush; Color